Development of an Adaptive Monitoring System for Cabled Observatories in the Laizhou Bay - CHEN Jie; Lü Bin; LIU Chao; LIU Hai-lin (Guangtongxin yanjiu, 2022)
This paper develops an adaptive and extensible remote monitoring system for seafloor observatory network in the Laizhou Bay marine ranch to realize long-term, continuous and on-line monitoring for marine ranch environment. According to the demand of seafloor observatory network, the control model of the remote monitoring system is established in this paper. And this paper creatively designs the communication mechanism, standardized communication protocol and dynamic management algorithm convenient for the plug and play of a large number of devices in the seafloor observatory network. The algorithm of data quality control is also improved. The application demonstration data of the marine ranch in Laizhou Bay shows that the package loss rate of the system is only 1%, and the success rate of instruction execution is as high as 98%. When adding, deleting and modifying seafloor devices, the system can complete the mapping and analysis data within 2 minutes. At the same time, the data quality control algorithm can effectively eliminate outliers and reduce the error rate to 0.000 81%. The successful application example of Laizhou Bay Marine ranch proves the performance and applicability of the system. It shows that the relevant algorithms in this paper can also be used in other similar systems with adaptive requirements.